Theoretical studies of the local structures and EPR parameters for Cu^{2+} center in Cd_{2}(NH_{4})_{2}(SO_{4})_{3} single crystal - Ch.-Y. Li (Condensed Matter Physics, 2015)
The electron paramagnetic resonance (EPR) parameters (g factors g_{i} and the hyperfine structure constants A_{i}, i = x, y, z) are interpreted by using the perturbation formulae for a 3d^{9} ion in rhombically (D_{2h}) elongated octahedra. In the calculated formulae, the crystal field parameters are set up from the superposition model, and the contribution to the EPR parameters from the admixture of d-orbitals in the ground state wave function of the Cu^{2+} ion was taken into account. Based on the calculation, local structural parameters of the impurity Cu^{2+} center in Cd_{2}(NH_{4})_{2}(SO_{4})_{3} (CAS) crystal were obtained (i.e., R_{x} ≈ 2.05 Å, R_{y} ≈ 1.91Å, R_{z} ≈ 2.32 Å). The theoretical EPR parameters based on the above Cu^{2+}-O^{2-} bond lengths in CAS crystal show a good agreement with the observed values. The results are discussed.